Inhibition of Nitrifiers and Methanotrophs from an Agricultural Humisol by Allylsulfide and Its Implications for Environmental Studies - Neufeld, Josh D. (American Society for Microbiology, 1999)
Allylsulfide, an inhibitor of ammonia monooxygenase, was tested to determine its ability to inhibit nitrification and methane oxidation in pure cultures, in agricultural humisol enrichment cultures, and in humisol slurries. We confirmed that allylsulfide is a differential inhibitor of cultures of nitrifiers and methanotrophs at concentrations of 1 and 200 μM, respectively, which result in 50% inhibition. However, although a nitrifying enrichment culture added to sterilized humisol was inhibited 50% by 4 μM allylsulfide, 500 μM allylsulfide was necessary for 50% inhibition of the endogenous nitrifying activity in nonsterile humisol. We concluded that native nitrifiers were protected, possibly by being in colonial aggregates or sheltered microenvironments.